A Cross-Sectional Study on Knowledge and Use of Contraception in Damoh District, Madhya Pradesh, India - Rahul Mishra; Hemant Patidar (Space and Culture, India, 2024)
Ensuring universal access to sexual and reproductive health (SRH) is one of the 17 Sustainable Development Goals (SDGs) to be achieved by 2030, adopted by the United Nations. Women’s improved reproductive health is positively associated with their knowledge and adoption of contraceptives. Contraception is crucial in determining the family size, birth interval, and women's health and falls under SDG3 and SDG5. This study aimed to highlight the knowledge and use of contraceptives in the Damoh district located in  Madhya Pradesh, India. We utilised primary data collected through a personal survey using a structured Interview Schedule from eight sampling units in the district. For this, we employed descriptive statistics and regression techniques for the analysis. Results reveal that a substantial share of women had knowledge of at least a single method of contraception. However, female sterilisation and pills were the most commonly known methods for women. Nonetheless, the knowledge of contraception was not found to be reflected in the adoption as nearly one-third of all women were not using any method of contraception. Further, the level of adoption of different contraceptive methods varied across socio-demographic backgrounds. Therefore, emphasis on information, education and communication (IEC) initiatives may lead to an increase in the adoption of modern contraceptives.